Spleen Tyrosine Kinase Inhibition Ameliorates Tubular Inflammation in IgA Nephropathy - Yiu, Wai Han; Chan, Kam Wa; Chan, Loretta Y. Y.; Leung, Joseph C. K.; Lai, Kar Neng; Tang, Sydney C. W. (Frontiers in Physiology, 2021)
Spleen tyrosine kinase (Syk) is a non-receptor tyrosine kinase involved in signal transduction in a variety of immune responses. It has been demonstrated that Syk plays a pathogenic role in orchestrating inflammatory responses and cell proliferation in human mesangial cells (HMC) in IgA nephropathy (IgAN). However, whether Syk is involved in tubular damage in IgAN remains unknown. Using human kidney biopsy specimens, we found that Syk was activated in renal tubules of biopsy-proven IgAN patients with an increase in total and phosphorylated levels compared to that from healthy control subjects. In vitro, cultured proximal tubular epithelial cells (PTECs) were stimulated with conditioned medium prepared from human mesangial cells incubated with polymeric IgA (IgA-HMC) from patients with IgAN or healthy control. Induction of IL-6, IL-8 and ICAM-1 synthesis from cultured PTECs incubated with IgA-HMC conditioned medium was significantly suppressed by treatment with the Syk inhibitor R406 compared to that from healthy control. Furthermore, R406 downregulated expression of phosphorylated p65 NF-κB and p-42/p-44 MAPK and attenuated TNF-α-induced cytokine production in PTECs. Taken together, our findings suggest that Syk mediates IgA-HMC conditioned medium-induced inflammation in tubular cells via activation of NF-κB and p-42/p-44 MAPK signaling. Inhibition of Syk may be a potential therapeutic approach for tubulointerstitial injury in IgAN.